Using a Participatory Learning and Action Approach to Improve Young Papuans and Moluccans’ Knowledge of Herbal Drinks to Increase Immunity During the COVID-19 Pandemic - Rully Adi Nugroho; Sri Kasmiyati; Elizabeth Betty Elok Kristiani; Vincentia Irene Meitiniarti; Agna Sulis Krave (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
The introduction of coronavirus disease (COVID-19) into the human population represents a tremendous medical and economical crisis. The immune system plays a central role in protecting against this novel virus. This activity aimed to empower young generation using participatory learning and action approach to improve their knowledge about medicinal plants that grow in Indonesia and whose anti-inflammatory, antioxidant, immunomodulatory, and antiviral properties. Organoleptic test results showed that Kunyit Asam (consisted of turmeric and ginger) and Tealang (consisted of butterfly pea and lemongrass) were highly favored by panelists. Our results provide valuable information on the medicinal plants used as an immunity booster within the studied community.